Megaesophagus Secondary to Feline Dysautonomia (Key-Gaskell Syndrome) in a Cat - Schaefer, Gabriela da Cruz; Gerardi, Daniel Guimarães; Castro, Neusa Barbosa; Guimarães, Lorena Lima Barbosa; Sonne, Luciana; da Costa, Fernanda Vieira Amorim (Acta Scientiae Veterinariae, 2016)
Background: Feline dysautonomia is a rare autonomic neuropathy of unknown cause, that has already been reported in Europe, the United States and Brazil. Cats usually show nonspecifc clinical signs that are associated with autonomic dysfunction of the nervous system. The diagnosis is based on the clinical signs and imaging tests, and confrmed by necropsy and histopathological fndings. The prognosis is poor and there is no defnitive treatment. The aim of this report is to describe a case of feline dysautonomia with emphasis in the clinical, diagnostic imaging and histopathological fndings. Feline dysautonomia must always be considered as a differential diagnosis in cases of megaesophagus in cats. Case: A mixed-breed young male cat was evaluated for anorexia, regurgitation, bilateral nasal discharge and dyspnoea for 24 h. The animal was dehydrated and had pale mucous membranes, abdominal distension and keratoconjunctivitis sicca. The neurological examination was normal. Abdominal ultrasound showed a distended bladder and normal intestinal motility. Chest radiography and esophageal contrast study exhibited megaesophagus in the intrathoracic region. Blood work showed mild neutrophilic leukocytosis and the presence of toxic neutrophils. The cat remained hospitalized for supportive care, including ﬂuidtherapy, broad spectrum antibiotics, antiemetic and mucosal protective drugs. Twelve days after the admission, the cat presented prostration, hypoglycemia, hypothermia, hypokalemia and severe leukopenia. Chest radiography revealed increased radiopacity in the right hemithorax, suggesting aspiration pneumonia. The cat died and during necropsy there was marked megaesophagus, with areas of erosion/ulceration of the mucosa, in addition to pulmonary consolidation areas. The histopathological analysis showed an extensive area of ulceration in the esophageal epithelium, in addition to infltration of lymphocytes, macrophages and occasional neutrophils and numerous bacteria, compatible with ulcerative esophagitis. The lung analysis showed severe multifocal thrombosis, multifocal areas of athelectasia, moderate congestion and edema, vegetable material in the bronchi, basophilic myriad bacterial and multifocal necrosis. Hypereosinophilic neurons with pyknotic nuclei, mild cytoplasmic vacuolization, loss of granular appearance of Nissl substance and nuclei shifted to the periphery were observed in the esophageal ganglia. The post mortem diagnosis was megaesophagus and chronic active esophagitis with neuronal degeneration, confrming the diagnosis of feline dysautonomia and aspiration pneumonia. Discussion: This cat was presented with nonspecifc clinical signs, megaesophagus, constipation, keratoconjunctivitis sicca and regurgitation that are commonly observed in cases of feline dysautonomia. However, there were also expiratory dyspnoea, which is less common. Unlike most cases, this cat did not show mydriasis, prolapsed nictitating membranes, reduced pupillary light response or bradycardia. Considering the evolution of its clinical condition, it was suspected that the cat died due to sepsis, possibly as a result of aspiration pneumonia. Since feline dysautonomia is uncommon and requires histopathological analysis for diagnosis confrmation, the prevalence of the disease might be underestimated in our region. In this case, the clinical evaluation, diagnostic imaging, macroscopic and histopathological fndings were consistent with dysautonomia, therefore it is important to consider the disease as a differential diagnosis in cases of megaesophagus in cats, even in the absence of other classical signs of autonomic dysfunction. Keywords: ganglioneuropathy, autonomic neuropathy, neurology, cat.